Clinical presentation and diagnosis of neuropathic pain - Barros, Guilherme Antônio Moreira De (2016)
ABSTRACTBACKGROUND AND OBJECTIVES: Neuropathic pain is reason for distress and incapacity of several patients, being that symptoms, mechanisms and management distinguish it from nociceptive pain. This study aimed at discussing the clinical presentation and diagnosis of neuropathic pain.CONTENTS: Neuropathic pain is manifested by several symptoms, being continuous burning pain, shock sensation and mechanical alodynia the most common ones. Neurophysiologic studies and skin biopsy suggest that burning pain is reflex of spontaneous activity of afferent nociceptive fibers, while shock sensation is originated from high frequency ectopic stimuli, generated in demyelinated Aβ fibers. Clinical exam, made up of history and elementary physical neurological evaluation, is critical for the adequate diagnosis of the type of pain, as well as more detailed exams, such as quantitative sensory tests and confocal optic microscopy, may bring further subsidies to the diagnosis of the type of pain.CONCLUSION: Clinical presentation of neuropathic pain has characteristics which help the accurate diagnosis of the syndrome or disease responsible for the onset of the complaint. Adequate clinical evaluation, including directed physical neurologic exam, sensory quantitative tests and cornea confocal microscopy cooperate for a more accurate diagnosis.